Structural organization of the thyroid gland and interrenal tissue with reference to endocrine parenchyma in short mackerel, Rastrelliger brachysoma (Bleeker, 1851) - Senarat, Sinlapachai; Kettratad, Jes; Na Lampang, Phakorn; Gettongsong, Tanita; Karnjanapak, Chanoknard; Palasai, Amphornphan; Kangwanrangsan, Niwat; Jiraungkoorskul, Wannee (Agriculture and Natural Resources, 2016)
The first investigations of the thyroid gland and interrenal tissue with reference to the endocrine parenchyma of short mackerel Rastrelliger brachysoma were subjected to histological analysis. Specimens were collected during the fishing season (October to November 2013) from the Upper Gulf of Thailand. Under a light microscope, the thyroid gland of R. brachysoma was distinctly found located within the branchial region. Within this gland, it consists of several follicles among afferent brachial arteries. Each follicle exclusively contained a colloid that was surrounded by a simple, cuboidal, follicle epithelium. Histological study showed that the localization of interrenal tissue was in the anterior kidney. This tissue was composed of two parts based on the structural compositions and cell types; (i) the stromal compartment was constituted of various interrenal cells and (ii) the interstitial compartment contained the connective tissue, leucocytes and blood sinuses, with reference to the lymphatic tissue.